IMPLEMENTASI PROBLEM BASED LEARNING MELALUI CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Awwaliya, Sella 'Izzata; Ah, Nurul Imamah; Purnomo, Edy (Prodi Pendidikan Matematika FKIP Universitas Madura, 2025)
This study aims to improve the mathematics learning outcomes of grade XI students at SMA Muhammadiyah 3 Jember through the implementation of Problem Based Learning (PBL) learning model integrated with Culturally Responsive Teaching (CRT) approach. This research is a Classroom Action Research (PTK) conducted in two cycles with each cycle harmonizing the stages of planning, implementation, observation, and reflection based on the Kemmis and McTaggart model. The research subjects were 30 students of class XI D. Data were generated through pretest and posttest in each cycle. The results showed an increase in the average learning outcomes of students and the percentage of classical completeness. In cycle I, the average score increased from 64 as the pretest score to 75 as the posttest score with completeness increasing from 30% to 53%. In cycle II, the average score increased from 70 as the pretest score to 86 as the posttest score with completeness increasing from 40% to 87%. This increase shows that the application of Problem Based Learning (PBL) integrated with Culturally Responsive Teaching (CRT) is effective in improving students' learning outcomes in the learning process through a cultural context that is relevant to their lives.Keywords: Problem Based Learning, Culturally Responsive Teaching, Learning Outcomes, Mathematics, Classroom Action Research